The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1001/archinternmed.2009.263
|View full text |Cite
|
Sign up to set email alerts
|

Timely Follow-up of Abnormal Diagnostic Imaging Test Results in an Outpatient Setting

Abstract: Background Given the fragmentation of outpatient care, timely follow-up of abnormal diagnostic test results remains a challenge. We hypothesized that an EMR that facilitates the transmission and availability of critical imaging results through either automated notification (alerting) or direct access to the primary report would eliminate this problem. Methods We studied critical imaging alert notifications in the outpatient setting of a tertiary care VA facility from November 2007 to June 2008. Tracking soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
181
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 185 publications
(185 citation statements)
references
References 37 publications
4
181
0
Order By: Relevance
“…Improved visibility helps radiologists demonstrate the value they already currently provide [1,7]. Additional "value" through direct communication could result from a reduced number of intermediary communication errors, decreased delays in patient management, reduced patient stress and anxiety, and improved patient adherence to follow-up recommendations [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved visibility helps radiologists demonstrate the value they already currently provide [1,7]. Additional "value" through direct communication could result from a reduced number of intermediary communication errors, decreased delays in patient management, reduced patient stress and anxiety, and improved patient adherence to follow-up recommendations [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…First among these unknowns are the preferences of patients. Few studies have examined patients' preferences, and those that have, have yielded conflicting results [8][9][10][11][12][13]. Additionally, most previously published studies involved surveys of outpatients at single institutions, resulting in narrowly selected groups of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, in our prior work on determining delayed follow-up of abnormal laboratory (including TSH) and imaging results, we found that most instances without documented follow-up were truly instances where no follow-up occurred, as confirmed with the providers. 12,13,15 Second, due to limited resources, our study did not involve a review of trigger-negative records, precluding the ability to assess the trigger's negative predictive value, sensitivity, or specificity. However, the use of the trigger still allowed us to identify 163 delays in care that otherwise would not have been found.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, their use has not eliminated follow-up delays, even when health care providers acknowledge receipt of notifications, a technological limitation of EHRs. 13 Indeed, our prior work revealed that 7-8% of EHR-based abnormal test result notifications were not acted on within 4 weeks. 14,15 Cognitive limitations of providers also contribute to delays in followup: for example, providers are often unable to discern relevant versus irrelevant information when assessing the need for follow-up while also dealing with information overload and alert fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…We previously identified ambiguity of responsibility for test result follow-up to be a key factor in failure to follow up abnormal results. 4 Several EHRs now use asynchronous alert notifications to transmit results, but providers often receive many other types of notifications in their electronic in-box. We found that primary care providers (PCPs) receive a mean of 57 alerts a day in an integrated delivery system's EHR, all with new information they need to process and/or act upon.…”
mentioning
confidence: 99%